Narrative discourse of the Israel-Palestine issue in the framework of political communication: A comparative study of Kompas.id and BBC media - Putra, Ariandi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
The Israel-Palestine conflict remains one of the most persistent and contentious geopolitical issues in the Middle East, with no clear resolution in sight. As a result, the conflict has become a focal point for media coverage, with various outlets striving to present objective and neutral reporting. However, it is important to recognize that the media is not free from bias, as each outlet carries its own perspective shaped by political, cultural, and economic factors. This study aims to investigate how Kompas.id and BBC News report on the Israel-Palestine conflict, particularly focusing on the events that occurred in October and November. By employing a critical content analysis approach, the study examines several articles published by both Kompas.id and BBC. The findings indicate that while both media outlets cover the same conflict, they offer differing perspectives and agendas. These differences may lead to varying interpretations of the conflict among readers, potentially influencing public opinion and fostering bias toward one side. The analysis highlights the role of media in shaping political narratives and the importance of critical media consumption. To gain a more well-rounded understanding of the conflict, it is essential for readers to consult diverse sources, including those with contrasting viewpoints. ***** Konflik Israel-Palestina masih menjadi salah satu masalah geopolitik yang paling persisten dan kontroversial di Timur Tengah, dan belum ada penyelesaian yang jelas. Akibatnya, konflik tersebut menjadi titik fokus pemberitaan media, dan berbagai media berupaya menyajikan pemberitaan yang obyektif dan netral. Namun, penting untuk menyadari bahwa media tidak bebas dari bias, karena setiap media mempunyai perspektifnya sendiri yang dibentuk oleh faktor politik, budaya, dan ekonomi. Penelitian ini bertujuan untuk mengetahui bagaimana Kompas.id dan BBC News memberitakan konflik Israel-Palestina, khususnya dengan fokus pada peristiwa yang terjadi pada bulan Oktober dan November. Dengan menggunakan pendekatan analisis konten kritis, penelitian ini mengkaji beberapa artikel yang diterbitkan oleh Kompas.id dan BBC. Temuan ini menunjukkan bahwa meskipun kedua media tersebut meliput konflik yang sama, keduanya menawarkan perspektif dan agenda yang berbeda. Perbedaan-perbedaan ini dapat menyebabkan beragamnya penafsiran konflik di kalangan pembaca, sehingga berpotensi mempengaruhi opini publik dan menumbuhkan bias ke satu pihak. Analisis ini menyoroti peran media dalam membentuk narasi politik dan pentingnya konsumsi media yang kritis. Untuk mendapatkan pemahaman yang lebih menyeluruh mengenai konflik ini, penting bagi pembaca untuk berkonsultasi dengan berbagai sumber, termasuk sumber-sumber yang memiliki sudut pandang berbeda.